2014
DOI: 10.1111/1477-9552.12090
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Consumer Preferences for Nanotechnology and Genetic‐modification Technology in Food Products

Abstract: This study investigates heterogeneous consumer preferences for nanofood and genetically‐modified (GM) food and the associated benefits using the results of choice experiments with 1,117 US consumers. We employ a latent class logit model to capture the heterogeneity in consumer preferences by identifying consumer segments. Our results show that nano‐food evokes fewer negative reactions compared with GM food. We identify four consumer groups: ‘Price Oriented/Technology Adopters’, ‘Technology Averse’, ‘Benefit Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Many studies have also found that consumers are willing to pay (WTP) a premium for GM food labeling or to avoid GM foods (reviewed in Colson and Rousu 2013). In a recent study using choice experiments, we found that US consumers are willing to pay more to avoid both GM and nano-foods, with a higher premium to avoid GM foods than nano-foods (Yue et al 2014). The political context for GM food labeling in the United States is becoming more and more contentious as state mandatory labeling bills are proposed, publicly challenged, and fiercely opposed by agri-business companies (Allen and Cummins 2012).…”
Section: Introductionmentioning
confidence: 80%
“…Many studies have also found that consumers are willing to pay (WTP) a premium for GM food labeling or to avoid GM foods (reviewed in Colson and Rousu 2013). In a recent study using choice experiments, we found that US consumers are willing to pay more to avoid both GM and nano-foods, with a higher premium to avoid GM foods than nano-foods (Yue et al 2014). The political context for GM food labeling in the United States is becoming more and more contentious as state mandatory labeling bills are proposed, publicly challenged, and fiercely opposed by agri-business companies (Allen and Cummins 2012).…”
Section: Introductionmentioning
confidence: 80%
“…Regarding production practices, consumers are generally willing to pay a premium for organic or nongenetically modified products as well as reduced use of hormones and antibiotics compared to some conventional practices or no given information (Ding, Veeman, & Adamowicz, ; Lim et al, ; Miller et al, ; Ortega et al, ; Probst et al, ; Wu et al, ; Zanoli et al, ). Recently, these practices have also considered nanotechnology (Erdem, ; Yue, Zhao, & Kuzma, ). Preferences differ by consumer segmentation including purchase habits, product types, socio‐demographics (e.g., Arnoult, Lobb, & Tiffin, ; Van Loo, Caputo, Nayga, Meullenet, & Ricke, ), and concerns over production practices (Chung, Briggeman, & Han, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with this view, UK consumers favour the idea of combining FT and organic labels (Sirieix et al, 2013). There is also an increasing amount of literature examining environmental eco‐labels or certification (Tait et al, ; Ubilava et al, ; Van Loo, Caputo, Nayga, Seo, & Verbeke, ) and improved environmental standards in food production (Moser, Schaefers, & Meise, ; Viegas et al, ; Yue et al, ; Tait, Saunders, & Guenther, ). Many of these studies found a positive WTP for environmental attributes, particularly for domestic products (Ortega et al, ; Uchida, Onozaka, Morita, & Managi, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that although the public is skeptical of the use of nanomaterials in food (for improving safety or enhance nutrition), is in better standing compared to the GMOs. [92••]…”
Section: Introductionmentioning
confidence: 99%